Spatial-Temporal Dynamics of Hepatitis E Virus Infection in Foxes (Vulpes vulpes) in Federal State of Brandenburg, Germany, 1993–2012 - Eiden, Martin; Dähnert, Lisa; Spoerel, Susanne; Vina-Rodriguez, Ariel; Schröder, Ronald; Conraths, Franz J.; Groschup, Martin H. (Frontiers in Microbiology, 2020)
Hepatitis E virus (HEV) is the main course for acute hepatitis in humans throughout the world. Human associated genotypes 1 and 2 as well as zoonotic genotypes 3 and 4 are grouped in the Orthohepevirus species A. In addition, a large variety of HEV-related viruses has been found in vertebrates including carnivores, rats, bats and chickens, which were classified in Orthohepevirus species B-D. In 2015, partial genome sequences of a novel hepevirus were detected in feces of red foxes (Vulpes vulpes). However, no further information about virus circulation and the prevalence in foxes was available. We therefore assayed a unique panel of 880 transudates, which was collected from red foxes over 19 years (1993-2012) in Brandenburg, Germany, for HEV-related viral RNA and antibodies. Our results demonstrate a high antibody prevalence of HEV in red foxes, which oscillated annually between 40% and 100%. Molecular screening of the transudates revealed only a single RNA-positive sample, which was assigned to the carnivore Orthohepevirus C genotype based on the amplified partial sequence. These data indicate that the virus is circulating widely in the fox population and that foxes are carriers of this virus.